Underage college students’ alcohol displays on Facebook and real-time alcohol behaviors - Moreno, Megan A. (J Adolesc Health, 2015)
PURPOSE: College is often a time of alcohol use initiation as well as displayed Facebook alcohol references. The purpose of this longitudinal study was to determine associations between initial references to alcohol on social media and college students’ self-reported recent drinking, binge drinking and excessive drinking. METHODS: First-year students from two US public universities were randomly selected from registrar lists for recruitment. Data collection included 2 years of monthly Facebook evaluation. When an initial displayed Facebook alcohol reference was identified, these “New Alcohol Displayers” were contacted for phone interviews. Phone interviews used the validated TimeLine FollowBack method to evaluate recent alcohol use, binge episodes and excessive drinking. Analyses included calculation of positive predictive value and Poisson regression. RESULTS: A total of 338 participants were enrolled, 56.1% were female, 74.8% were Caucasian and 58.8% were from the Midwestern university. A total of 167 (49.4%) participants became New Alcohol Displayers during the first two years of college. Among New Alcohol Displayers, 78.5% reported past 28-day alcohol use. Among New Alcohol Displayers who reported recent alcohol use, 84.9% reported at least one binge episode. Posting an initial Facebook alcohol reference as a profile picture or cover photo was positively associated with excessive drinking (RR=2.34, 95% CI: 1.54–3.58). CONCLUSIONS: Findings suggest positive associations between references to alcohol on social media and self-reported recent alcohol use. Location of initial reference as a profile picture or cover photo was associated with problematic drinking, and may suggest that a student would benefit from clinical investigation or resources.